[Charlotte Street, Port of Spain, Trinidad, B.W.I.] - Lanks, Herbert (My University, 2010)
Description the back of the postcard: "Overhanging balconies protect shoppers from sun and rain."
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Pedestrians--Trinidad and Tobago; Stores, Retail--Trinidad and Tobago; Charlotte Street